Classification of irreducible non-dense modules for A₂⁽²⁾ - Bunke, T. (Algebra and Discrete Mathematics, 2009)
We obtain a classification of the supports of irreducible A₂⁽²⁾-modules. In particular, we get a classification of all non-dense irreducible A₂⁽²⁾-modules with at least one finite-dimensional weight subspace.